EUPHEMISM IN CNN ONLINE NEWSPAPER - Javier Tuerah (Fakultas Bahasa dan Seni, Universitas Negeri Manado, 2021)
This research aims at identifying euphemisms as figurative language and explain their types and functions in CNN Online Newspaper. This research applied descriptive method. In the data gathering, this study applied purposive sampling technique. The subject of this research was nine news items published in CNN official site with time range of July 2021. Based on the findings, the most frequent type of euphemism used by the news writer was negative euphemisms with eleven data (55%) and the least type was positive euphemism with nine data (45%). This shows the commonness of figurative language use in social life especially in online media as public scope. From the entire news data, several news contain more than two and more euphemisms and the rest have less than two euphemisms. Since figurative language especially euphemism is effective for maintaining harmonious social relationship language users, the use of euphemistic expressions are highly recommended for any purpose as professionals especially lecturers and students as well as language users.